Adverse effects to quality of life arising from treatment can recover with intermittent androgen suppression in men with prostate cancer. - Spry, N.; Kristjanson, Linda; Hooton, B.; Hayden, L.; Neerhut, G.; Gurney, H.; Corica, T.; Korbel, E.; Weinstein, S.; McCaul, Kieran (Elsevier, 2006)
Health-related quality of life (HQOL) research is a means of broadening the assessment of treatment effects. This longitudinal study investigated the dynamic change to quality of life (QOL) and testosterone dependant physiology in men commencing an intermittent maximal androgen blockade program (IMAB). Two hundred and fifty men were accrued to the multi-centre study of IMAB (Flutamide 250 mg TDS, Leuprolide 22.5 mg depot) ceasing treatment after 9 months if PSA <4 ng/ml, and restarting when PSA >20 ng/ml. QOL was assessed every 3 months for 30 months using the EORTC QLQ-C30 and EORTC QLQ-PR25 module. Data completion for the whole study was 90%. At baseline, our cohort was less symptomatic and had better function than the EORTC reference cohort, which may be related to a shift in clinical practice with time. Testosterone suppression (AS) lead to a significant reduction in global HQOL and deterioration in most function and symptom scales. During the off period, there was a trend of progressive improvement in HQOL that paralleled testosterone recovery but was slower than the rate of deterioration during the treatment phase. Maximum recovery of HQOL occurred most frequently by months 9-12. Testosterone recovery was slower and less complete in older men, and lead to concomitant poorer HQOL recovery. Whilst the magnitude of mean change to scale scores was small, there was a consistent and simultaneous deterioration during maximal androgen blockade (MAB) and improvement during androgen recovery. Older men are more likely to show an impaired testosterone recovery, and this was paralleled by a slower HQOL recovery. Newer methods of analysis to describe results in a way that has meaning to the individual patient are warranted.